(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The peak of tuberculosis infection activity in the world occurred at the end of the 20th century. Tuberculosis is recognized by WHO as a global problem, causing colossal economic and biological damage. If 20’ years ago the world saw a decrease in tuberculosis morbidity and mortality rates, then currently 1/3 of the population is infected with Mycobacterium tuberculosis The epidemiological situation of tuberculosis in different regions of the world is constantly changing as a result of the complex relationship between population movement, the number and distribution of patients with tuberculosis who excrete bacteria , the socio-economic and cultural level of the population, the availability of medical care, and the prevalence of HIV infection.